2017
DOI: 10.1101/196295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-term stabilities of 21 amino acids in dried blood spots

Abstract: BACKGROUND: Dried blood spots (DBSs) have potential use in remote health applications for individual and population diagnosis, and can enable epidemiological surveillance for known and unknown diseases. The preparation and transportation of DBSs from remote settings often exposes these cards to extreme environmental stress that may impact the quality of the diagnostic data. Given these risks, it is essential to investigate the individual stabilities of biomarkers in DBSs. This paper details the stability of ro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Peptides were purified using HPLC and the parent mass to charge ratio confirmed using an Ultraflex III-MALDI TOF/TOF Mass Spectrometer (Bruker LTD., Milton, ON). The purity of each peptide was determined using capillary zone electrophoresis on a 7100 Capillary Electrophoresis System (Agilent Technologies), as previously described (30,31), and the absolute concentration of each peptide was measured in-house using LC/MS-based amino acid analysis (32). Briefly, peptide standards were acid hydrolyzed and the resulting amino acids were dansylated (32) and subjected to HPLC-MS/MS (1290 Infinity HPLC online with 6490 triple Quad MS) (Agilent-Technologies) operated in dynamic MRM mode.…”
Section: Methodsmentioning
confidence: 99%
“…Peptides were purified using HPLC and the parent mass to charge ratio confirmed using an Ultraflex III-MALDI TOF/TOF Mass Spectrometer (Bruker LTD., Milton, ON). The purity of each peptide was determined using capillary zone electrophoresis on a 7100 Capillary Electrophoresis System (Agilent Technologies), as previously described (30,31), and the absolute concentration of each peptide was measured in-house using LC/MS-based amino acid analysis (32). Briefly, peptide standards were acid hydrolyzed and the resulting amino acids were dansylated (32) and subjected to HPLC-MS/MS (1290 Infinity HPLC online with 6490 triple Quad MS) (Agilent-Technologies) operated in dynamic MRM mode.…”
Section: Methodsmentioning
confidence: 99%
“…5a). This is due to the oxidizing effect of thioester group of different amino acids present in feather hydrolysate [27]. This study indicated good stabilities of liquid fertilizer during the temperature transitions.…”
Section: Field Trialsmentioning
confidence: 67%
“…This indicates that the amino acids recovered from the synthesized DPS systems are very comparable with those from the pure plasma. Some amino acids are away from the diagonal line probably owing to the following combined effects: (a) compared to pure plasma, the Absorbent 2 may have unspecific binding to some amino acids; (b) amino acid concentrations could change in DBS cards during the drying process with the changes varying among different amino acids 55 ; and (c) similar to albumin protein recoveries, there might be underestimations of plasma recoveries in the lab‐made systems due to the evaporation of plasma during the weighting process.…”
Section: Resultsmentioning
confidence: 99%